(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2025)
Otolith associations have been extensively described from the Badenian (Langhian to early Serravallian) of the Central Paratethys. During the late Badenian (early Serravallian), the basin was strongly segmented, and the faunal composition of its biota differed remarkably from one area to another. Here I describe otoliths from a historical collection from the late Badenian of Walbersdorf (Austria) that represents the only known deepwater fish fauna of the Central Paratethys of the time. It is species-rich (66 species) and unique in its composition characterized by a high percentage of mesopelagic and bathydemersal fishes (10 and 15 species respectively). The otolith assemblage offers new insights into how the fish fauna reacted to the ecological crisis of the middle Badenian salinity event (early Serravallian). It was also the last time in geological history that the Central Paratethys was connected to the Mediterranean through the Slovenian Gate. Faunal composition, environmental adaptation, and biostratigraphic implications are discussed in the context of the fish evolution in the Paratethys and other European basins. In addition, 11 new species are described (in order of description): Palaspius extremus n. gen. n. sp. (Leuciscidae), Gymnoscopelus septentrionalis n. sp. and Krefftichthys walbersdorfensis n. sp. (both Myctophidae), Physiculus pinnatus n. sp. (Moridae), Lophiodes pitassyae n. sp. (Lophiidae), Cataetyx lacrimatus n. sp. (Bythitidae), Sargocentron viennensis n. sp. (Holocentridae), Globogobius praeglobosus n. sp. (Gobiidae), Cubiceps huimanni n. sp. (Nomeidae), Prionotus friedmani n. sp. (Triglidae), and Malacanthus bratishkoi n. sp. (Malacanthidae).